Strategi Pemerintah Desa Dalam Menanggulangi Penyebaran Virus Covid-19 di Desa Sukaluyu Kecamatan Telukjambe Timur Kabupaten Karawang - Liawati Liawati; Lukmanul Hakim; Gun Gun Gumilar (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study discusses the Village Government Strategy in Overcoming the Spread of the Covid-19 Virus in Sukaluyu Village, Karawang Regency. The purpose of this study is to find out and examine what kind of strategy the Sukaluyu Village Government is implementing in tackling the spread of the Covid-19 virus. This study uses a qualitative method with a descriptive approach. The author uses data collection techniques in the form of literature studies, observations, interviews, and documentation studies. This study was analyzed using the Theory of Strategic Management which was bought by Fred R. David (2017:4) with three indicators namely, strategy formulation, strategy implementation and strategy evaluation. The results of the research regarding the Village Government's Strategy in Overcoming the Spread of the Covid-19 Virus in Sukaluyu Village, Karawang Regency have not run optimally starting from the stages of strategy formulation, strategy implementation and strategy evaluation. This is due to the absence of a written vision and mission and the absence of village regulations in handling Covid-19 made by the village government as a supporting initial capital in developing strategies. The dissemination of socialization on prevention of Covid-19 was uneven and irrational, and the evaluations carried out did not produce constructive changes.